Cortico-limbic pain mechanisms. - Thompson, Jeremy M. (Neurosci Lett, 2018)
Pain has a strong emotional component and is defined by its unpleasantness. Chronic pain represents a complex disorder with anxio-depressive symptoms and cognitive deficits. Underlying mechanisms are still not well understood but an important role for interactions between prefrontal cortical areas and subcortical limbic structures has emerged. Evidence from preclinical studies in the rodent brain suggests that neuroplastic changes in prefrontal (anterior cingulate, prelimbic and infralimbic) cortical and subcortical (amygdala and nucleus accumbens) brain areas and their interactions (corticolimbic circuitry) contribute to the complexity and persistence of pain and may be predetermining factors as has been proposed in recent human neuroimaging studies.